Features of the Supply Chain Development in the Areas of Oil Production and Refining - I. L. Beilin; M. Sh. Tagirov; R. I. Zinurova; V. V. Khomenko; N. M. Yakupova (International Journal of Supply Chain Management, 2020)
Abstract— The oil industry is one of the most important industries, which are the main export goods of Russia. The oil and gas industry is involved in a global supply-chain that includes domestic and international transportation, ordering and inventory visibility and control, materials handling, import/export facilitation and information technology. In addition, the price of the third main component of exports of natural gas substantially depends on the level of prices for oil and oil products. The oil industry of the Russian Federation is closely connected with all sectors of the national economy, and therefore is of great importance for the Russian economy. The demand for oil is always ahead of the offer, so almost all developed countries in the world are interested in the successful development of our oil industry. The object of the research of this article is to organize the supply chain management development in the areas of oil production and refining. The subject of research is the territorial organization of oil production and refining. The purpose of the work is to analyze the territorial organization of oil production and refining in Russia. The goal of the research involves the solution of the following main tasks: To study the theoretical and methodological issues of the oil industry; Identify geographic differences in the distribution of petroleum resources; to substantiate ways to improve the territorial organization of oil production and refining in Russia. The organization of the development of the supply chain management in the areas of oil production and refining is characterized by significant features. These include issues of investment policy and the development of innovations, the efficiency of managing production clusters, the tax structure in this sector of the economy, the supply chain foreign economic activity and others.